Improving elementary school students' mathematical problem-solving skills: The effectiveness of realistic mathematics education with problem-based learning - Hanifah, Hanifah; Maryadi, Adi (Jurnal Gantang, 2025)
Mathematics education in Indonesian elementary schools faces significant challenges in developing students' problem-solving skills, as evidenced by the 2022 PISA results, which showed that only 18% of Indonesian students achieved the minimum proficiency level, far below the OECD average. This study aims to evaluate the effectiveness of integrating the Realistic Mathematics Education (RME) approach with Problem-Based Learning (PBL) to enhance fourth-grade students' mathematical problem-solving skills in Bekasi Regency. A quasi-experimental design with a nonequivalent control group was employed, involving 52 students selected through cluster random sampling. The experimental class received RME-based PBL instruction, while the control class received PBL instruction based on the scientific approach. Data were collected using a validated problem-solving essay test and analyzed using descriptive and inferential statistics, including independent-samples t-tests and normalized gain scores. The results demonstrated that the RME-PBL approach significantly improved students' problem-solving skills across all measured aspects: problem identification, formulation, strategy application, and result explanation. Notably, 92% of students in the experimental class achieved good or very good categories, compared to only 22.22% in the control class. The normalized gain for the experimental class was 0.81 (high category), substantially higher than the control class's 0.41 (moderate category). It is concluded that the RME-PBL approach is significantly more effective than the scientific-PBL approach in enhancing elementary students' mathematical problem-solving abilities.